Value of Transesophageal 3D Echocardiography as an Adjunct to Conventional 2D Imaging in Preoperative Evaluation of Cardiac Masses - Müller, Silvana; Feuchtner, Gertrud; Bonatti, Johannes; Müller, Ludwig; Laufer, Günther; Hiemetzberger, Renate; Pachinger, Otmar; Barbieri, Verena; Bartel, Thomas (Echocardiography (Mount Kisco, N.Y.), 2008)
Background: This study sought to compare three‐dimensional (3D) and two‐dimensional (2D) transesophageal echocardiography (TEE) to assess intracardiac masses. It was hypothesized that 3D TEE would reveal incremental information for surgical and nonsurgical management. Methods: In 41 patients presenting with intracardiac masses (17 thrombi, 15 myxomas, 2 lymphomas, 2 caseous calcifications of the mitral valve and one each of hypernephroma, hepatocellular carcinoma, rhabdomyosarcoma, lipoma, and fibroelastoma), 2D and 3D TEE were performed, aiming to assess the surface characteristics of the lesions, their relationship to surrounding structures, and attachments. Diagnoses were made by histopathology (n = 28), by computed tomography (n = 8), or by magnetic resonance imaging (n = 5). Benefit was categorized as follows: (A) New information obtained through 3D TEE; (B) helpful unique views but no additional findings compared to 2D TEE; (C) results equivalent to 2D TEE; (D) 3D TEE missed 2D findings. Results: In 15 subjects (37%), 3D TEE revealed one or more items of additional information (category A) regarding type and site of attachment (n = 9, 22%), surface features (n = 6, 15%), and spatial relationship to surrounding structures (n = 8, 20%). In at least 18% of all intracardiac masses, 3D TEE can be expected to deliver supplementary information. In six patients, additional findings led to decisions deviating from those made on the basis of 2D TEE. In 11 subjects (27%), 3D echocardiographic findings were categorized as “B.” Conclusions: Information revealed by 3D imaging facilitates therapeutic decision making and especially the choice of an optimal surgical access prior to removal of intracardiac masses.